2023
DOI: 10.1101/2023.05.04.539450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid pathology impairs experience-dependent inhibitory synaptic plasticity

Abstract: Alzheimer's disease is associated with altered neuronal activity, presumably due to impairments in homeostatic synaptic plasticity. Neuronal hyper and hypoactivity are also observed in mouse models of amyloid pathology. Using multicolor two-photon microscopy, we test how amyloid pathology alters the structural dynamics of excitatory and inhibitory synapses and their homeostatic adaptation to altered experience-evoked activity in vivo in a mouse model. The baseline dynamics of mature excitatory synapses and the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…However, prolonged visual deprivation (≥5 days) triggers reorganization of visual circuits in adult rodents, including increased NR2b/NR2a ratio, reduced GluR2/GABA A ratio (He, Hodos and Quinlan, 2006), and retraction of inhibitory dendrites or synapses (Chen et al, 2011; Keck et al, 2011; van Versendaal et al, 2012), which together may lower the threshold for neuronal activation (Bridi et al, 2018). Additionally, we recently found that one week of visual deprivation elicited accelerated inhibitory synapse loss in WT mice but not hAPP mice (Niraula, Yan and Subramanian, 2023). Here, we found that c-Fos + cell density consistently and sharply increased in WT but not hAPP mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, prolonged visual deprivation (≥5 days) triggers reorganization of visual circuits in adult rodents, including increased NR2b/NR2a ratio, reduced GluR2/GABA A ratio (He, Hodos and Quinlan, 2006), and retraction of inhibitory dendrites or synapses (Chen et al, 2011; Keck et al, 2011; van Versendaal et al, 2012), which together may lower the threshold for neuronal activation (Bridi et al, 2018). Additionally, we recently found that one week of visual deprivation elicited accelerated inhibitory synapse loss in WT mice but not hAPP mice (Niraula, Yan and Subramanian, 2023). Here, we found that c-Fos + cell density consistently and sharply increased in WT but not hAPP mice.…”
Section: Discussionmentioning
confidence: 99%
“…The presented in vivo presynaptic structural data is an independent analysis performed from the same raw dataset acquired as previously described (Niraula et al, 2023a; Niraula et al, 2023b). TdTomato-filled axons were first identified based on branch morphology and absence of postsynaptic markers, then en passant and terminaux boutons were manually labeled based on morphology using a modified version of the ObjectJ plugin (Villa et al, 2016) for FIJI (Schindelin et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations